2003
DOI: 10.1046/j.1469-0691.2003.00703.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus segnis: a rare cause of endocarditis

Abstract: This report presents a case of endocarditis due to Haemophilus segnis, which represents a speciation difficulty for the routine laboratory. In this study, a molecular approach provided speciation, which was confirmed phenotypically by a reference laboratory. The use of molecular genotypic analysis is an additional strategy in the investigation of endocarditis. It has applications not only in isolate identification but also in primary detection of infection, particularly in patients whose blood is culture negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…It has been reported by our group and others that the nomenclature may differ based on the technology used (30). The fact that the species identified in our study, including Leptotrichia goodfellowii, N. flavescens, N. subflava, A. segnis, Campylobacter showae, and Capnocytophaga granulosa, have been associated with extraoral infections involving hematogenous transmission, such as endocarditis, meningitidis, and extraoral abscesses (2,16,19,36,50,53), indicates their ability to translocate to different body parts and their virulence potential.…”
Section: Discussionmentioning
confidence: 62%
“…It has been reported by our group and others that the nomenclature may differ based on the technology used (30). The fact that the species identified in our study, including Leptotrichia goodfellowii, N. flavescens, N. subflava, A. segnis, Campylobacter showae, and Capnocytophaga granulosa, have been associated with extraoral infections involving hematogenous transmission, such as endocarditis, meningitidis, and extraoral abscesses (2,16,19,36,50,53), indicates their ability to translocate to different body parts and their virulence potential.…”
Section: Discussionmentioning
confidence: 62%
“…H. influenzae is a more common etiology of adult bacteremia than other Haemophilus and Aggregatibacter spp. combined (213); consequently, the isolation of H. influenzae from blood is rarely a sign of infective endocarditis, and the species is sometimes omitted from the HACEK group (126,214 (210,215,216).…”
Section: Infectious Endocarditis and The Hacek Groupmentioning
confidence: 99%
“…In many situations, 16S rDNA sequencing is the ultimate solution to identification of aetiological agents of infectious diseases caused by rarely encountered bacteria [11][12][13][14][15][16][17][18][19][20][21][22]. This not only allows correct identification and selection of appropriate treatment, but also contributes to a better understanding of the epidemiology and pathogenic role of these bacteria, which has not been possible in the past.…”
Section: E T H O D Smentioning
confidence: 99%
“…In another study, six cases of ‘ S. milleri ’ endocarditis were attributed to S. anginosus , suggesting that S. anginosus had the highest propensity to cause infective endocarditis among the three species of the ‘ S. milleri group’ [62]. Using this ‘state‐of‐the‐art’ technique, it was also found that Haemophilus segnus is an important cause of non‐ H. influenzae bacteraemia [19,63,64]. In addition, the use of 16S rDNA sequencing for clinically ‘unidentifiable’ bacteria could have clinical significance regarding the choice of antibiotic regimen as well as the duration of treatment.…”
mentioning
confidence: 99%